Law No. 30 Of The Year 1975 Regarding The System Of The Suez Canal Authority As Amended By Laws Nos. 11/1976 And Decree Of The President Of The Republic No. 34/2014 = قانون رقم 30 لسنة 1975 بنظام هيئة قناة السويس معدل بالقوانين رقم 11/1976 و 4/1998 وقرار رئيس الجمهورية رقم 34/2014 - Egypt; The middle east library for economic services, translator. (2025)
Law no. 30 of the year 1975 regarding the system of the Suez Canal Authority As Amended By Laws Nos. 11 of the year 1976 and 4 of the year 1998 and decree of the president of the republic no. 34 of the year 2014 قانون رقم 30 لسنة 1975 بنظام هيئة قناة السويس معدل بالقوانين رقم 11 لسنة 1976 و رقم 4 لسنة 1998 وقرار رئيس الجمهورية رقم 34 لسنة 2014